Health Needs Assessment Plan for Pregnant Women in Low-Income Sub-Saharan Africa - Anoh, Chinedu Okorie; Parsa, Ali Davod; Kabir, Russell; Hayhoe, Richard (Queeva Publishing, 2025)
Maternal mortality remains a devastating public health challenge across Sub-Saharan Africa. Nigeria, in particular, accounts for nearly 20% of global maternal deaths, with a maternal mortality ratio (MMR) estimated at over 800 deaths per 100,000 live births (WHO, 2019). In Katsina State, recent hospital-based reviews report an MMR of approximately 1,200 per 100,000 live births, with hypertensive disorders and lack of antenatal care as leading contributors (Adeoye et al., 2025). This crisis is not merely statistical—it reflects systemic neglect, social inequity, and preventable loss. A Health Needs Assessment (HNA) offers a structured, evidence-based approach to uncovering these gaps and guiding targeted interventions. In Katsina, retrospective analyses show that over 68% of maternal deaths occurred in women who were not booked for antenatal care, and nearly half died within 24 hours of hospital presentation. These findings underscore the urgency of community-level engagement and early intervention. To move from data to action, multi-sectoral collaboration is essential. Corporate Social Responsibility (CSR) initiatives can play a transformative role in bridging funding and service gaps. The Centre for Social Justice (CSJ) has documented Katsina’s MNCH budget allocations and highlighted the disconnect between policy standards and actual health outcomes (CSJ, 2016). By aligning CSR investments with HNA priorities—such as mobile outreach, midwife training, and health literacy campaigns—private sector actors can contribute meaningfully to maternal health equity. This model is not unprecedented. CSR-health partnerships have yielded measurable improvements in maternal outcomes in India and Kenya (Ameh et al., 2012). Nigeria’s private sector, particularly in extractive and telecom industries, has the capacity to replicate and scale such interventions. What’s needed is political will, ethical commitment, and strategic alignment with community needs. Maternal mortality is not an inevitable consequence of poverty—it is a failure of systems, priorities, and imagination. A well-executed HNA, backed by CSR engagement and policy accountability, can reshape maternal health trajectories in Katsina and across low-income Sub-Saharan Africa. Let this be the moment we reframe maternal health not as a distant development goal, but as a shared responsibility—grounded in evidence, driven by compassion, and sustained by collaboration.